2003
DOI: 10.1080/13550280390195388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Epidemiology and Survival of Progressive Multifocal Leukoencephalopathy in the Era of Highly Active Antiretroviral Therapy: Data from the Italian Registry Investigative Neuro AIDS (IRINA)

Abstract: Human immunodeficiency virus (HIV)-associated progressive multifocal leukoencephalopathy (PML) remains a relevant clinical problem even in the era of highly active antiretroviral therapy (HAART). Aims of the study were to analyze clinical and treatment-related features and the survival probability of PML patients observed within the Italian Registry Investigative Neuro AIDS (IRINA) during a 29-month period of HAART. Intravenous drug use, the presence of focal signs, and the involvement of white matter at neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(51 citation statements)
references
References 32 publications
5
44
1
1
Order By: Relevance
“…Several case series have evaluated cidofovir as a treatment against PML with good results [2,9,10], and some reports showed an improvement under a therapy with cidofovir after progression of PML under HAART [8,20,22,24,31]. In contrast, in a prospective non-randomized pilot study [19], a retrospective multicenter cohort study [30], and in a retrospective observational study [3], cidofovir did not prolong survival in patients with PML.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several case series have evaluated cidofovir as a treatment against PML with good results [2,9,10], and some reports showed an improvement under a therapy with cidofovir after progression of PML under HAART [8,20,22,24,31]. In contrast, in a prospective non-randomized pilot study [19], a retrospective multicenter cohort study [30], and in a retrospective observational study [3], cidofovir did not prolong survival in patients with PML.…”
Section: Discussionmentioning
confidence: 95%
“…However, in previous studies, highly active anti-retroviral therapy (HAART) led to an improved outcome in AIDS-associated PML [3,5,13]. Contradictive results have been published on a possible additional efficacy of cidofovir [2,3,9,10,12,19,23,30]. Cidofovir is an acyclic nucleoside phosphonate with highly selective activity against mouse polyomaviruses in vitro [1,6,7,27], but on the other hand, cidofovir showed only minimal effect in toxic concentrations for the target cell against JC virus replication or multiplication in an immortalized human neuroglial cell line [17].…”
Section: Introductionmentioning
confidence: 93%
“…5,[36][37][38] In recent years, many studies have documented improved survival rates among PML patients who receive HAART. 31,[37][38][39][40][41][42][43] This association may be strongest when therapy includes a protease inhibitor. 44 There are some factors associated with prolonged survival in patients with PML: use of HAART, high CD4 cell count at time of diagnosis, increase of CD4 cell count by O100 cell/ml, low HIV viral load, PML as initial AIDS diagnosis, low JC virus levels in CSF, clearance of JC virus from CSF and lack of neurological progression 2 months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HAART has been recognized as the only intervention to have a significant impact in PML outcome. Survival beyond 1 year increased from just below 10% (Berger et al, 1998b) to 50% (Antinori et al, 2003). Interestingly, unlike other opportunist infections, the incidence of PML was not affected by HAART, and a recent study showed PML as the third cause of neurological disease in HIV-infected patients after CNS toxoplasmosis and HIV encephalopathy (Antinori et al, 2003).…”
Section: Pml In the Aids Eramentioning
confidence: 96%